Financial asset allocation and green innovation - Jun Duan; Tingting Liu; Xiaoran Yang; Hua Yang; Yunwei Gao (Green Finance, 2023)
Sustainable development is a key issue of global concern, and countries around the world are striving to promote green development. From the perspective of financial asset allocation motivation, this paper explores the impact of financial asset allocation on green innovation based on the data of A-share listed non-financial companies from 2011 to 2021. First, there is an inverted U-shaped relationship between the proportion of financial asset allocation and the green innovation of physical enterprises, that is, as the proportion of financial asset allocation increases, the green innovation output of enterprises first increases and then decreases. After robustness testing, the conclusion still holds. Second, further testing of the intermediary mechanism shows that the moderate holding of short-term financial assets by real enterprises can increase the output of green innovation by alleviating financing constraints, which is manifested as the "reservoir" effect. The "crowding out" effect plays a leading role when overallocation of financial assets reduces liquidity supply and capital expenditure, which in turn reduces green innovation output. Third, in the test of financial asset allocation preference, it is found that the short-term financial assets held by enterprises mainly play a "reservoir" effect, that is, they tend to be "preventive" motives. Holding long-term financial assets mainly exerts a "crowding out" effect, that is, tends to "seek profits" motives. Finally, there are differences in the impact of financial asset allocation on green innovation output among enterprises with different property rights, different monetary policies and different social responsibilities.